Question #1545

When trying to find "x" and "y", how would i use the substitution method in a problem such as

x=y+3 and 2x-y=5 (same problem not two different ones)

x=y+3 and 2x-y=5 (same problem not two different ones)

Expert's answer

You have to substitute x=y+3 into the second equation:

2(y+3)-y = 5

2y + 6 - y = 5

y = 5-6 = -1

Thus x = -1+3 = 2.

**Answer: (2,-1)**

2(y+3)-y = 5

2y + 6 - y = 5

y = 5-6 = -1

Thus x = -1+3 = 2.

Learn more about our help with Assignments: AlgebraElementary Algebra

## Comments

## Leave a comment